2018
DOI: 10.1002/rcs.1892
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted vs freehand pedicle screw fixation in spine surgery – a systematic review and a meta‐analysis of comparative studies

Abstract: Three randomized controlled trials (RCTs) and six retrospective comparative studies included a total of 750 patients (3625 pedicle screws). No significant differences were noted between RA and FH in pedicle screw accuracy (95.5% compared with 92.9%; odds ratio: 1.35; 95% confidence interval [CI], 0.55 to 3.30; P=0.51), overall complication rate (1.33% compared with 3.45%; odds ratio: 0.46; 95% CI, 0.15 to 1.43; P=0.18) and radiation exposure time (weighted mean difference [WMD]:8.49; 95% CI, -15.43 to 32.40; P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 40 publications
4
70
0
Order By: Relevance
“…The longer surgical duration of the RA group could be attributed to more intraoperative preparation work needed for the robot system. Longer surgical time has also been noted in other robot systems for spine surgery. In the FG group, the intraoperative blood loss was significantly higher than in the RA group.…”
Section: Discussionmentioning
confidence: 66%
“…The longer surgical duration of the RA group could be attributed to more intraoperative preparation work needed for the robot system. Longer surgical time has also been noted in other robot systems for spine surgery. In the FG group, the intraoperative blood loss was significantly higher than in the RA group.…”
Section: Discussionmentioning
confidence: 66%
“…The accuracy of screw placement has been widely investigated. In a recent meta-analysis, Yu et al 14 compared 2,062 thoracic and lumbar pedicle screws implanted in 750 patients using RAN or FH technique. They found that only 4.6% of RAN screws breached > 2 mm from the predicted trajectory compared to 16% of screws placed by FH techniques.…”
Section: Discussionmentioning
confidence: 99%
“…RAN has been originally used in spine surgery for the placement of lumbar pedicle screws in spinal fusion. 14 Still, pedicle screw insertion is not the only field of application. Indeed, RAN has been proved to be a safe technique for spinal decompression, oncologic spine surgery, and MISS including cage positioning.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis from Gao et al of six randomized controlled trials, involving 688 PSs in 158 patients in the robot‐assisted group and 672 PSs in 148 patients in the freehand group, demonstrated equal accuracy, less radiation exposure during surgery, but a longer surgical duration of the robot‐assisted PSs. Yu et al analysed three randomized controlled trials and found no significant differences between robot‐assisted and fluoroscopy‐guided PS implantation regarding accuracy. Also in this study, robot‐assistance was associated with a longer operative time but had a shorter radiation exposure time.…”
Section: Discussionmentioning
confidence: 99%